Pengembangan Learning Management System pada SMK PGRI 2 Badung - Ni Putu Linda Santiari; I Gede Surya Rahayuda; I Putu Ramayasa (LPPM Universitas Bumigora, 2022)
SMK PGRI 2 Badung is one of the schools that has been established in 1997. The current COVID-19 pandemic has resulted in the closure of schools as places to carry out teaching and learning activities. It forces the ministry of education to think of alternatives to continue the teaching and learning process. The utilization of e-learning can improve learning outcomes to the maximum. Likewise, SMK PGRI 2 Badung utilizes e-learning with an online learning platform, namely Google Classroom. Learning using Google Classroom encourages teachers to think creatively in delivering material and practicum. Online learning is done using Google Classroom with virtual face-to-face learning using Google Meet. However, for the collection of all school learning data, Google Classroom is lacking because the data storage of school learning activities is not centralized. For school archives, teachers still collect files to schools manually so that reporting is less structured and centralized. From the results of the analysis and interviews conducted, the author intends to do service with the title Training and mentoring for LMS development at SMK PGRI 2 Badung. The LMS that will be developed is an LMS with Moodle. Service activities are focused on developing the Moodle LMS, and training and mentoring the use of Moodle LMS. Activities are carried out using lecture, question and answer methods, and direct practice. From the LMS development and training activities, it was found that SMK PGRI 2 Badung has an independent LMS in the learning process, namely learning-smkpgri2badung. Sch. id and 80% of teachers can use Moodle LMS to help the learning process.